EXAMINATION OF TOTAL PETROLEUM HYDROCARBON DEGRADATION IN A POLLUTED STAGNANT SALT AND FRESH WATER MEDIA - Ulakpa, Wisdom Chukwuemeke (Chemical Engineering Journal Storage (CEJS), 2024)
The total petroleum hydrocarbon (TPH) levels were estimated in a stationary aquatic environment that consisted of a mixture of saltwater and freshwater, using the principles of first-order kinetics. The dispersion of total petroleum hydrocarbon (TPH) was studied in the presence of water using a transportation model that considered both convective and diffusion variables. This model was utilised to monitor the concentration of TPH in both the vertical and horizontal dimensions. Thus, it was anticipated that diffusion would exclusively govern the transport or dispersion of TPH in the horizontal direction, while both diffusion and convection induced by gravity would govern TPH transport in the vertical direction. The rate of TPH degradation was analysed using first-order degradation rate kinetics and the Monod model. In this study, we simulated and compared the projected TPH degradation along both vertical and horizontal orientations. The TPH values in the vertical direction were obtained at a specified time and then compared to the experimental data. The purpose of this was to determine the system that best corresponded to the TPH levels measured in the experiment. This study has demonstrated that employing first-order kinetics is a successful approach for monitoring, predicting, and modelling the breakdown of total petroleum hydrocarbons in a stagnant water environment affected by sedimentation.